Micelles mediated separation fluorimetric methodology for Rhodamine B determination in condiments, snacks and candies - Alesso, Magdalena (2012)
Dye Rhodamine B (RhB) has been widely used in textile industry and foodstuffs but due to its proved carcinogenicity and toxicity on human, many countries have forbidden its use in foods. A new methodology is proposed for Rhodamine B (RhB) fluorimetric determination applying separation with a surfactant. Experimental parameters that affect the separation and determination steps like surfactant concentration, time and temperature of equilibration, pH of extraction, nature and composition of diluting agent of surfactant rich phase have been studied and optimised. The implementation of separation step permitted to remove successfully the interferences of matrix components, improving selectivity and sensitivity. Developed methodology presents a linearity range between 4.67 × 10 -2 and 100 μg L -1 with a correlation coefficient of 0.999. At optimal experimental conditions, a LOD of 1.40 × 10 -2 μg L -1 and LOQ of 4.67 × 10 -2 μg L -1 were obtained, allowing RhB determination in a variety of commercial condiments, snacks and bubble gums.